(untitled) (Journal of the Bangladesh Agricultural University, 2011)
Two pot and two field experiments were conducted at Patuakhali Science and Technology University research farm to investigate the contribution of tidal submergence to phosphorus nutrition and yield of rice. Pot and field experiments were conducted in the Aus and Aman seasons of 2009, respectively. The factorial experiments include two levels of water source- i) tidal water and ii) ground water, and three levels of fertilizers- i) absolute control (no fertilizer), ii) NK (P omission) and iii) NPK (P addition). The rice varieties used were BRRI dhan27 (HYV) and Local Mala (Traditional variety) in Aus season and BR23 (HYV) and Lalmota (Traditional variety) in Aman season. A general increase in growth, yield and yield contributing parameters were found due to irrigation with tidal water. Tidal water contributed about 21 (BR23) and 7 (Lalmota) % higher grain yield in Aman season 2009 and about 2 g biomass yield per pot (both BRRI dhan27 and Local Mala) in Aus season of 2009 compared to ground water. Phosphorus content of rice grain and straw was always higher when plants are irrigated with tidal water. In general tidal submergence increases P uptake of rice. Phosphorus uptake from tidal water treatments increased when plants were supplied with N and K fertilizer. Tidal submergence contributed about 5-6 kg P/ha in P omission plot, and about 12-14 kg P/ha in plots with added P. Keywords: Phosphorus; Rice; Tidal submergence DOI: 10.3329/jbau.v8i2.7927 J. Bangladesh Agril. Univ. 8(2): 207-212 2010